The Effect Of Administrative Sanctions And Modernization Of The Tax Administrative System On Motor Vehicle Taxpayer Compliance At Samsat Office Haurgeulis Kabupaten Indramayu - Fahrul Alam Masruri; Milasar Milasar (LPPM Universitas Sebelas April, 2023)
This study aims to determine: (1) The Effect of Administrative Sanctions on Motor Vehicle Taxpayer Compliance. (2) The Effect of Modernisation of the Tax Administration System on Motor Vehicle Taxpayer Compliance. (3) The Effect of Administrative Sanctions on the Modernisation of the Tax Administration System. (4) The Effect of Administrative Sanctions and Modernisation of the Tax Administration System on the Compliance of Motor Vehicle Taxpayers at SAMSAT Office, Haurgeulis, Indramayu Regency. The method used in this study is a quantitative method using survey research method approach with a sample of 100 taxpayers. The data analysis method used is multiple linear regression analysis with the help of SPSS 26 program. The results obtained from this study indicate that (1) Administrative Sanctions have a positive and significant effect of 63.4% on Motor Vehicle Taxpayer Compliance. (2) Modernisation of the Tax Administration System has a positive and significant effect of 67.1% on Motor Vehicle Taxpayer Compliance. (3) Administrative Sanctions have a positive and significant effect of 53.6% on the Modernisation of the Tax Administration System. (4) Administrative Sanctions and Modernisation of the Tax Administration System have a positive and significant effect of 55.6% on Motor Vehicle Taxpayer Compliance. From the results of hypothesis testing, it can be concluded that Administrative Sanctions and Modernisation of the Tax Administration System have a positive effect on Motor Vehicle Taxpayer Compliance, meaning that taxpayers accept the policies that have been determined by the government.